Preparasi Pelepah Sawit Untuk Bahan Baku Pembuatan Wood Plastic Composite (WPC) Ditinjau Dari Konsentrasi Asam Oksalat Dan Suhu Pelarutan - Angelina Angelina; Bahruddin Bahruddin; Said Zul Amraini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Components contained in the palm stem are cellulose, hemicellulose, lignin, and other extractive substances. Cellulose is the largest component of palm fronds. Preparation is used to remove components of hemicellulose and lignin and extractive substances there by increasing the cellulose component which will increase the strength of the interface on the matrix and filler. The purpose of this study was to study the effect of oxalic acid concentration and dissolution temperature on the chemical composition of palm stem in the preparation of palm stem which will be used as raw material of wood plastic composite. Samples of palm stem preparations were prepared using oxalic acid at concentrations of 0,5 M, 1 M, and 1,5 M. Samples were immersed in 15 min with dilution temperature is room temperature, 800C, 1000C, and 1200C. Then the sample size of palm stem dust used is 40 mesh. Tests include water content test and chemical composition test of palm stem using chesson-data method. The test results show that the water content in the palm stem sample is 5% -10%. While for the best composition of the palm stem obtained by preparation using oxalic acid with concentration of 1,5M at dissolving temperature of 1200C that is obtained cellulose level as much as 54%.Keywords : palm stem, cellulose, preparation, wood plastic composite